Peningkatan Hasil Belajar IPA dengan Model Problem Based Learning Siswa Kelas VIII SMP - Desinta Dwi Nuriyanti; Abdul Haris; Asmawati Asmawati; Muhiddin P (Universitas Negeri Makassar, 2024)
This study aims to determine the effect of the combination of plasticine and video media on the learning outcomes of 8th graders on the Excretory System material. The type of research applied is classroom action research with 15 students in class 8B SMP Negeri 1 Kutasari. Video is used as a description of the problem that will be solved using the Probem Based Learning (PBL) model. Data collection was carried out using student learning outcomes with multiple choice items based on google form. The data collected was then analyzed by statistic qualitative descriptive analysis and obtained an average score of learning outcomes in the first cycle of 42.67. In the cycle I, plasticine was used to reconstruct the nephron model. In cycle 2 obtained an average score of 67.31 in this case an increase in the value of learning outcomes in cycle II when compared to cycle I. The increase also occurred in cycle III. The learning outcomes of the cycle III are 91.67. Classical completeness with KKM 70 in the cycle II is 20%, the cycle II is 46.67%, and the cycle III is 100%. From the results of this study, it can be concluded that the PBL model can improve student learning outcomes.